Pengaruh Brain Gym terhadap Peningkatan Fungsi Kognitif pada Lansia dengan Risiko Demensia di Panti Sosial Tresna Werdha Budi Mulia1 - Rahmatika , Hanifa; Puput Dinda Kurniawan, Ganesa; Laela Abida, Liza (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Decreased cognitive function is one of the impacts of the aging process in the elderly, which begins with a decrease in memory. This can also have an impact on the decline in the ability to speak, understand space, and the ability to judge and pay attention will result in inhibition of long-term memory and information processing in the elderly. If not treated properly, the decline in cognitive function can lead to dementia which results in decreased intellectual function and memory. Brain Gym is a collection of movement exercises that increase blood flow and oxygen to the brain, and stimulate the right and left brain to improve concentration and memory. Objectives: To determine the effect of Brain Gym on improving cognitive function in elderly people at risk of dementia at PSTW Budi Mulia 1. Methods: This study used a pre-experimental method with a one group pre-test and post-test approach. A total of 18 people who have met the inclusion and exclusion criteria. Measuring instrument used MMSE. Results: Of all the research objects, the average result of cognitive function before intervention was 17.94 and after intervention 24.72. Hypothesis testing shows there is an effect of Brain Gym on improving cognitive function. Conclusion: Brain Gym has an effect on improving cognitive function in elderly people with dementia risk at Panti Sosial Tresna Werdha Budi Mulia 1. Keywords: Cognitive function, Elderly, Elderly at Risk of Dementia, Brain Gym